The culture of heritage conservation in Malaysia: a study of eco-tourism in Langkawi - Chan, Geraldine K.L.; Sivapalan Selvadurai,; Rahimah Abdul Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Conservation of heritage resources requires immense human effort; more so now if it has become a neccesity for socio-economic development and ultimately human survival. However, humans can no longer work in silo and social isolation for conservation. Instead, they have to work together to conserve natural and cultural resources as much as they can, as hard as they can. However, as rapid urbanisation and modernisation can create challenges in heritage conservation despite technological advancement, more human effort is required than before. Humans can get back to age old efforts that have withstood test and time, i.e. efforts that are cultural and social in nature. The creation of a culture of heritage conservation is one such effort. Shared values, shared norms and cultural practices are common denominators for a culture of heritage conservation. Amongst various forms of cultural practices, social networking as a form that is common to all societies. Social networking that is based on social relationships is an inevitable fact of everyday social living in any society. Malaysian society is no different from any society in this sense, more so with valuable natural and cultural heritage resources to conserve. This article presents and discusses some findings from an empirical research on the presence of a culture of heritage conservation that facilitates a socio-economic activity, i.e. eco-tourism, in some parts of Langkawi. Langkawi which is acknowledged as a geopark by UENSCO is an archipelago of islands that is situated in the north of Peninsular Malaysia. The research found that the culture is based on particular shared values and shared norms that have been contributing to the growth of eco-tourism in the main island of Langkawi. The values and norms become the foundation of particular social networks among stakeholders involved in the eco-tourism. That networks eventually sustain and faciliate their social networking process. Hence, social networks are confirmed a key element in the cultural practice of social networking for organising and mobilising stakeholders to work together so that future generation can continue to reap the benefits of heritage conservation through ecotourism while sustaining heritage resources.